Is the permeability of crystalline rock in the shallow crust related to depth, lithology or tectonic setting?. Issue 1 (19th September 2014) - Ranjram, M.; Gleeson, T.; Luijendijk, E.
Abstract: The permeability of crystalline rocks is generally assumed to decrease with depth due to increasing overburden stress. While experiments have confirmed the dependence of permeability on stress, field measurements of crystalline permeability have not previously yielded an unambiguous and universal relation between permeability and depth in the shallow crust (<2.5 km). Large data sets from Sweden, Germany and Switzerland provide new opportunities to characterize the permeability of crystalline rocks in the shallow crust. Here we compile in situ permeability measurements ( n  =   973) and quantitatively test potential relationships between permeability, depth (0–2.5 km), lithology (intrusive and metamorphic) and tectonic setting (active and inactive). Higher permeabilities are more common at shallow depths (<1 km), but trend analysis does not support a consistently applicable and generalizable relationship between permeability and depth in crystalline rock in the shallow crust. Results suggest lithology has a weak control on permeability–depth relations in the near surface (<0.1 km), regardless of tectonic setting, but may be a more important control at depth. Tectonic setting appears to be a stronger control on permeability–depth relations in the near surface. Permeability values in the tectonically active Molasse basin are scattered with a very weak relationship between permeability and depth. While results indicate that there is no consistently applicable relationship between permeability and depth for crystalline rock in the shallow crust, some specific lithologies and tectonic settings display a statistically significant decrease of permeability with depth, with greater predictive power than a generalized relationship, that could be useful for hydrologic and earth system models. Abstract : The authors present a compilation of 973 in‐situ crystalline rock permeability measurements and quantitatively test potential relationships between permeability, depth, lithology, and tectonic setting in the shallow crust (<2.5 km). Results indicate that there is no consistently applicable relationship between permeability and depth in crystalline rock. Tectonic setting appears to be an important control on permeability‐depth relations in the upper 100 metres of the subsurface, while lithology may be a more important control at depth.